Solve

Asked by  | 22nd Jul, 2010, 07:35: PM

Expert Answer:

 Dear Student 
Solving by Cross multiplication

ax + by = a – b

 bx – ay = a + b

    Here, a1 = a                    b1  = b

       a2 = b                             b2 = -a

     c1 = a – b                        c2 = a + b

However Elimination method is easy to apply here as shown below

ax + by = a - b    ....(1)
bx - ay = a + b    .....(2)
Cross multiply (1) by b and (2) by a,
abx  + b2y = ab - b2
abx - a2y = a2 + ab
Now subtracting these two, we get
(a2+ b2)y = -(a2+ b2)
y = -1,
Using this in equation (1),
ax - b = a - b
we get x = 1.
Regards,
Team,
TopperLearning.

Answered by  | 23rd Jul, 2010, 10:52: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.